Evaluasi Pengaruh Elemen Arsitektur Terhadap Kenyamanan Visual Pengunjung Pada Kafe Berkonsep Arsitektur Industrial Di Surabaya - Bagas Klana Putra; Dr.Eng. Ir. Herry Santosa, ST., MT., IPM (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, 2024)
ABSTRACT In the current era of technological development, artistic and specific design forms make existing cafe buildings attractive. Various architectural design styles are widely used by cafes in the city of Surabaya. One of the architectural design styles that is quite popular and contemporary is the industrial concept which is currently very much in demand. Industrial design can provide a new atmosphere for visitors, apart from taking photos, it also provides comfort. Of the several cafes with this design that are famous and represent research objects, they are TGC Coffee, Historica Cafe and Zerogram Cafe. The elements of industrial architecture start from the structure of the building, the choice of materials used, color, model and arrangement of furniture, as well as other decorative elements used, including vegetation. Every visitor who comes must have a different level of comfort and have different perceptions. These perceptions can later be used as reference material to assess visitors' perceptions of visual comfort in terms of the visual elements in each cafe. Therefore, it is necessary to conduct research related to visual comfort. This research was carried out and the results are expected to be used as input for cafe business people who want to create cafes with an industrial concept. Based on the research results obtained from the three cafe research subjects, the principles of industrial architecture are the concepts used in the cafe building. Even though according to the results of an in-depth study, it was found that these principles were not completely one hundred percent of the industrial architectural concept actually implemented, this was due to the existence of other architectural concepts that accompanied and existed in the cafe. Keywords: Architectural Elements, Exterior, Interior, Industrial Architecture Concept.